Ash dark as night - Phillips, Gary, 1955- (Phillips, Gary, 1955- Harry Ingram mystery, 2024)
"Los Angeles, 1965. Tempers have boiled over in the Watts neighborhood, sparked by the traffic stop of two Black motorists, the Frye brothers, by the Highway Patrol. Freelance crime photographer Harry Ingram is on the scene, capturing images of the cops as they unleash batons, dogs, and water hoses on the predominantly Black crowd. When he snaps proof of an unarmed man being shot down by the LAPD, he winds up in the hospital, beaten, his camera confiscated. Proof of the killing seems lost--until Ingram's girlfriend, Anita Claire, retrieves the film roll in a daring rescue, and the photo makes front-page news. A recuperating Ingram is approached by Betty Payton, a comrade of Anita's mother, who wants Ingram's help tracking down her friend Moses "Mose" Tolbert. Ingram follows the investigation down a rabbit hole of burglary rings, bank robberies, looted cash, and city-wide conspiracies--all while grappling with his newfound fame, which puts him in the sightlines of LAPD's intelligence division. Boiling over with wry humor, fascinating historical details, and intimate atmosphere, Ash Dark as Night is a nail-biting ride-along through midcentury Los Angeles with a crime fiction legend in the driver's seat."--